SANKSI PIDANA TERHADAP TINDAK PIDANA PENYALAHGUNAAN BAHAN BAKAR BERSUBSIDI DI INDONESIA - Kodai, Dince Aisa; Suleman, Wilson (Journal Evidence Of Law, 2023)
The purpose of this writing is to examine the application of criminal sanctions against perpetrators of criminal acts of misuse of subsidized fuel based on Law Number 22 of 2001 concerning Oil and Natural Gas. The method used is normative juridical with a statute approach, which is carried out by examining all laws and regulations related to legal issues related to the issues to be studied. The results of the discussion explain that the use of subsidized fuel oil in Indonesia is regulated based on Law Number 22 of 2001 concerning Oil and Gas and various related regulations, including Presidential Regulation Number 117 of 2021 concerning the Third Amendment to Presidential Regulation Number 191 of 2014 concerning the Provision, Distribution and Retail Selling Prices of Oil Fuel, Minister of Energy and Mineral Resources Regulation No. 12 of 2012 concerning Control of the Use of Fuel Oil, Regulation of the Downstream Oil and Gas Regulatory Agency No. 3 of 2012 regulates the control of subsidized fuel types for cars used for plantation and mining activities, Regulation of the Regulatory Agency for Downstream Oil and Gas No. 4 of 2012 concerning the allocation of subsidized fuel volume, Downstream Oil and Gas Regulatory Agency Regulation No. 5 of 2012 concerning Guidelines for Issuing Letters of Recommendation, Regulation of the Minister of Energy, Mineral Resources No. 1 of 2013 concerning Control of the Use of Fuel Oil. Criminal sanctions for perpetrators of criminal acts of misuse of subsidized fuel based on Law Number 22 of 2001 concerning Oil and Gas, namely sanctions that can be imposed on perpetrators of abuse of subsidized fuel as regulated in Article 55.